The effect of Sharia green marketing and environmental awareness in fostering buying interest of Halal beauty product - Kadir, Syahruddin; Marzuki, Sitti Nikmah (Universitas Islam Indonesia, 2025)
IntroductionConsumers’ increasing concern for sustainability has created new demands for environmentally friendly products, particularly in the cosmetics industry. In Muslim-majority markets, Shariah-compliant green marketing has emerged as a strategic approach to align ethical values and environmental responsibility. However, limited studies have explored how environmental knowledge, word of mouth, and Shariah green marketing interact to influence purchase intention through the mediating role of environmental attitude.ObjectivesThis study investigates the direct and indirect effects of environmental knowledge, word of mouth, and Shariah green marketing on purchase intention, with environmental attitude as a mediating variable. It aims to contribute to the understanding of sustainable consumer behavior in a religious and ethical context.MethodA quantitative research design was adopted, utilizing a structured online questionnaire distributed to 260 Avoskin consumers. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The model assessed both measurement and structural components, including convergent validity, reliability, discriminant validity, path coefficients, and mediation analysis.ResultsThe findings show that Shariah green marketing had the strongest direct and indirect effects on purchase intention, followed by word of mouth. Environmental knowledge significantly influenced environmental attitude but did not directly affect purchase intention. Environmental attitude was confirmed as a key mediator in the relationship between the three exogenous variables and purchase intention.ImplicationsThe study highlights the critical role of environmental attitudes in bridging values-driven marketing with sustainable consumer behavior. It suggests that marketers should focus on emotional and ethical engagement to foster pro-environmental attitudes and stimulate purchase intention.Originality/NoveltyThis research enriches the current literature by integrating Islamic ethical marketing with sustainability discourse and consumer behavior theory. It offers new insights into how environmental and religious values jointly shape green purchasing behavior, particularly in emerging markets.